Sustainability Performance and Corporate Cost of Debt: The Role of ESG Scores and Capital Structure Moderation Evidence from the SRI-KEHATI Index - Hayati, Nur; Wardhana, M.Adhitya; Putri, Refika Anjani (Value Added : Majalah Ekonomi dan Bisnis, 2026)
This study investigates the relationship between Environmental, Social, and Governance (ESG) performance and corporate cost of debt, incorporating capital structure as a moderating variable and firm size as a control variable. Drawing upon signalling theory, the research examines whether ESG scores function as credible signals that reduce perceived credit risk and, consequently, borrowing costs. The analysis focuses on firms listed in the SRI-KEHATI Index over the period 2020–2024. Using Partial Least Squares Structural Equation Modelling (PLS-SEM) on a purposive sample of 35 companies, the study evaluates both direct and interaction effects within the proposed structural framework.The empirical findings indicate that ESG performance exerts a negative and statistically significant effect on the cost of debt, suggesting that firms with higher ESG scores benefit from lower borrowing costs. These results support the argument that sustainability performance reduces information asymmetry, enhances creditor confidence, and mitigates perceived default risk. While leverage (proxied by the debt-to-equity ratio) also demonstrates a significant association with borrowing costs, the interaction between ESG performance and capital structure is not statistically significant. This evidence implies that capital structure does not moderate the relationship between ESG and the cost of debt. Moreover, firm size does not exhibit a significant effect within the model.With an explanatory power of 60.9 per cent (R² = 0.609), the model demonstrates substantial robustness. Overall, the findings suggest that ESG practices contribute directly to debt financing efficiency, independently of leverage conditions. The study advances the literature on ESG and corporate finance by providing empirical evidence from an emerging market context and highlighting the direct role of sustainability performance in shaping borrowing costs.